(untitled) (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to verify the distribution of job descriptions, control of working hours, the effectiveness of limited labor, as well as factors supporting and hindering operations. A descriptive qualitative approach with a verification study design was applied in the Pakunden, Sukorejo Subdistrict, Blitar City. The research subjects included owners and employees at Dapur Mak Eco, Warung Bu Sinta, and Warung Biru. Data was collected through in-depth interviews, direct observation, and documentation using interview guidelines and structured observation instruments. Data analysis techniques included reduction, presentation, and drawing conclusions. The research findings indicate that job assignments are made verbally based on a sense of family trust, without a formal organizational structure. Time management faces challenges due to the extended actual working hours—from early morning until late at night—required for logistics preparation. Limited workforce effectiveness is achieved through collaborative work patterns and responsive multitasking capabilities during customer surges. The maturity of personnel’s technical skills and owner involvement are key supporting factors, while physical fatigue and conflicts with domestic roles act as barriers. The study’s conclusion affirms that an informal work system can maintain business stability through high flexibility, even though time efficiency remains suboptimal. Owners are advised to implement simple digital logistics tracking and scheduled technical training to reduce operational reliance on the owner’s presence.